2010
DOI: 10.1128/jb.00722-10
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Diesel-Degrading Acinetobacter sp. Strain DR1

Abstract: The genus Acinetobacter is ubiquitous in soil, aquatic, and sediment environments and includes pathogenic strains, such as A. baumannii. Many Acinetobacter species isolated from various environments have biotechnological potential since they are capable of degrading a variety of pollutants. Acinetobacter sp. strain DR1 has been identified as a diesel degrader. Here we report the complete genome sequence of Acinetobacter sp. DR1 isolated from the soil of a rice paddy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 9 publications
1
32
0
1
Order By: Relevance
“…Acinetobacter is metabolically versatile, and the ability of the members of this genus to degrade aliphatic hydrocarbons (e.g., crude petroleum and fuels, as well as aromatic hydrocarbons) has great potential for bioremediation studies (Jung et al, 2010). Jurelevicius et al (2013) showed that crude oil-and heptadecane-enriched operational taxonomic units in freshwater microcosms were represented mainly by the genus Acinetobacter.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter is metabolically versatile, and the ability of the members of this genus to degrade aliphatic hydrocarbons (e.g., crude petroleum and fuels, as well as aromatic hydrocarbons) has great potential for bioremediation studies (Jung et al, 2010). Jurelevicius et al (2013) showed that crude oil-and heptadecane-enriched operational taxonomic units in freshwater microcosms were represented mainly by the genus Acinetobacter.…”
Section: Discussionmentioning
confidence: 99%
“…CP000521; Smith et al, 2007). (Barbe et al, 2004), 'Acinetobacter oleivorans' DR1 (Jung et al, 2010), A. baumannii AB0057, AB900 and AB307-0294 (Adams et al, 2008), ACICU (Iacono et al, 2008), 17978 (Smith et al, 2007), and SDF and AYE (Vallenet et al, 2008). Table 1 provides specific strain descriptions.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of AoSoxR Target Genes-To identify SoxRregulated genes, we used the A. oleivorans genome and transcriptome data indicating possible SoxR binding sites (24,(31)(32)(33). Although five possible candidate promoters (AOLE_ 16635 encoding a putative L-PSP endoribonucleases, AOLE_ 18450 encoding a membrane protein, argT, scpA, and hisZ) were found using a putative SoxR binding site, two of them (scpA and hisZ) were not induced by RACs.…”
Section: Resultsmentioning
confidence: 99%